2014
DOI: 10.4236/ajps.2014.511183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Intensities of Drought Stress on δ<sup>13</sup>C Variation among Plant Organs in Rice: Comparison of Two Cultivars

Abstract: The δ 13 C value is widely used to assess the effects of drought on water status in plants. However, there is little information regarding the δ 13 C signature in different organs of rice. We conducted a field study to examine whether the δ 13 C among different plant parts would be affected by the intensities of drought, and to evaluate genotypic variation in δ 13 C fluctuation among plant parts affected by drought intensities. Two cultivars, "Nipponbare" (Oryzasativa ssp. japonica) and "Kasalath" (O. sativa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Elazab et al (2012) and Bort et al (2014) also showed a δ 13 C increase in flag leaves of different durum wheat genotypes under water stress at later growth stages, which could be associated with higher water-use efficiency (Araus et al, 2008, 2013; Tardieu, 2013; Bort et al, 2014). A stronger water stress does not always lead to larger changes in δ 13 C, particularly when analyzed in dry matter, as noted in previous studies in rice (Kano-Nakata et al, 2014) and Pinus tabuliformis (Ma et al, 2014). In addition, δ 13 C was strongly reduced at high [CO 2 ] because of the very negative δ 13 C of the CO 2 used to increase the [CO 2 ] within the growth chamber (Aljazairi et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Elazab et al (2012) and Bort et al (2014) also showed a δ 13 C increase in flag leaves of different durum wheat genotypes under water stress at later growth stages, which could be associated with higher water-use efficiency (Araus et al, 2008, 2013; Tardieu, 2013; Bort et al, 2014). A stronger water stress does not always lead to larger changes in δ 13 C, particularly when analyzed in dry matter, as noted in previous studies in rice (Kano-Nakata et al, 2014) and Pinus tabuliformis (Ma et al, 2014). In addition, δ 13 C was strongly reduced at high [CO 2 ] because of the very negative δ 13 C of the CO 2 used to increase the [CO 2 ] within the growth chamber (Aljazairi et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…The general trend of increasing 13 C in the flag leaf with drought stress found in our present study (Figure 3c) agrees with the results of previous studies on rice [39,40] and wheat [41,42]. As long as the δ 13 C and g s are closely related and the level of δ 13 C is determined by the stomata behavior [28,38,40], the decreased levels of δ 13 C of the desiccated plants could be explained in the same manner described above for the g s . The higher g s of the desiccated plants induced by the accumulation of proline and soluble sugars led to the lower values of δ 13 C observed for the desiccated plants.…”
Section: Effect On Stomatal Conductance and δ 13 Csupporting
confidence: 83%
“…There was no correlation between both g s and δ 13 C, and grain yield; possibly due to the use of only one genotype in this study, since that the cultivar effects on δ 13 C values depends on drought stress intensity, genotype and soil moisture content [40]. Therefore, the differences in δ 13 C value between drought stress and non-stressed conditions are critical.…”
Section: Effect On Stomatal Conductance and δ 13 Cmentioning
confidence: 99%
“…Drought stress had stronger effects on δ 13 C levels in sink parts such as roots and panicles than the other plant parts (Grant et al, 2012;Monti et al, 2006;Peuke et al, 2006), indicating that roots are the prominent sink for photo-assimilated carbon (Kano-Nakata et al, 2014). Kano-Nakata et al (2014) also reported that the plants that are well adapted to mild drought stress showed greater variance in carbon isotope ratio (δ 13 C) value among different plant parts. It is well established that such variation in δ 13 C among plant parts is related to the isotope fractionation during transport, the synthesis of metabolites, and the chemical composition such as the amounts of lipids, lignin and cellulose contents (Brugnoli & Farquhar, 2000) while the mechanism for the isotope fractionations is yet the subject for further study.…”
Section: Open Accessmentioning
confidence: 97%
“…drought could help plants maintain dry matter production (Kameoka et al, 2015) through more efficient root exploration in deeper soil and greater water acquisition, which may be closely linked with promoted carbon assimilate allocation to the deep roots during soil drying (Gowda et al, 2011;Zhu et al, 2010). Drought stress had stronger effects on δ 13 C levels in sink parts such as roots and panicles than the other plant parts (Grant et al, 2012;Monti et al, 2006;Peuke et al, 2006), indicating that roots are the prominent sink for photo-assimilated carbon (Kano-Nakata et al, 2014). Kano-Nakata et al (2014) also reported that the plants that are well adapted to mild drought stress showed greater variance in carbon isotope ratio (δ 13 C) value among different plant parts.…”
Section: Open Accessmentioning
confidence: 99%